Correlations between reaction wave propagation and phase formations in combustion of diluted TiO2–Al–C mixture - Saw, L.H.; Rahbari, R.G.; Abd Shukor, Mohd Hamdi; Yahya, Rosiyah (Maney Publishing, 2009)
The influence of Al 2O 3 diluent on quasi-adiabatic combustion synthesis of (3TiO 2+4Al+3.5C+yAl 2O 3) mixture in the presence of oxygen was studied. Assuming adiabatic conditions, maximum temperature of the system for y=0, 0.5, 1.0, 1.5, 2.0, and 2.5 was calculated. Activation energy of reaction kinetics was thermoanalytically determined based on thermogravimetric analysis. Boundary between steady/unsteady wave propagations in self-sustaining (SS) mode of combustion was determined for various amounts of diluents. Existing models proposed in combustion kinetics were used to relate propagation modes of combustion wave to activation energy and conversion rate. The examined model was successfully corresponded to additional phase formations in the product.